Abstracts of the 2024 Medical Association of Nigerians across Great Britain (MANSAG) Annual Educational Symposium on 11th May 2024: At Delta Hotels by Marriott Nottingham Belfry, United Kingdom. NG8 6PY - Alalade, Andrew (Journal of Global Medicine, 2024)
The Main Supplementary page is at Vol 4, No.S1 (2024), and this will lead to the landing pages of individual abstracts.